Festivity in the worldview of the Lithuanian language - Papaurėlytė-Klovienė, Silvija (Lietuvių kalba, 2025)
This article reveals a part of the content of the concept ŠVENTĖ (English: Festivity) which is related to the worldview of the Lithuanian language. The theoretical basis of the research consists of a cognitive linguistic approach to the relationship between the meaning of a word, a concept and a category, using conceptual analysis, descriptive and interpretive methods, as well as a free association experiment. The material under study consists of the field of associations of the word švęsti (English: to celebrate) and examples of the use of all forms of the adjectives šventiškas,-a (en. festive) and of the adverb šventiškai (English: festively), which reveal the actualisation of the category of festivity in language. It is believed that the content of a concept is most accurately revealed in the minds of language users by verbal associations, so the information obtained from the association field of the word švęsti forms the basis of the description, which is complemented by the insights gained from the analysis of the examples of the category actualisation.The concept ŠVENTĖ belongs to the type of mixed concepts – it is close to the typical scheme and scenario, therefore a two-part sequence has been chosen to describe the content of the concept. First, the reason for the celebration is described in the Lithuanian worldview, and then the manifestations of the celebration are discussed – the signs that suggest celebration.The conclusion is drawn that language users are not inclined to associate celebrations with occasions of national importance, and that there is a stronger orientation towards the sphere of private life.The linguistic worldview captures the notion that the process of celebration involves a variety of incomplete and unfinished activities with no clear outcome, an intense expression of emotions.
Keywords: concept; types of concepts; free association experiment; category of the festivity